(untitled) (Journal of Insurance Studies in South Asia, 2025)
This research investigates how adults in Nepal gain practical knowledge and financial awareness by directly engaging with non-life insurance products. It shifts focus from a purely theoretical interpretation of insurance literacy to viewing it as a learning process for adults influenced by their real-life experiences. Utilizing a qualitative narrative inquiry method, the study looks into how insured individuals develop their understanding through activities such as purchasing policies, paying premiums, filing claims, and interacting with insurance providers. Grounded in Adult Learning Theory, specifically Knowles’ andragogical model and Kolb’s experiential learning cycle, the research underscores the impact of readiness to learn, problem-based scenarios, and self-directed involvement on insurance literacy. Research findings indicate that adults often have a poor grasp of policy coverage, terminology, and claims processes, frequently swayed by inaccuracies, complicated policy language, and insufficient communication from institutions. Nevertheless, active participation over time increases awareness of risks, fosters financial responsibility, and enhances decision-making skills. The research highlights significant obstacles to the adoption of non-life insurance in Nepal, such as a lack of transparency, inadequate education at the community level, and restricted access to digital resources. It underscores the importance of insurance professionals serving as educators and trusted allies rather than just policy salespeople. By improving insurance literacy through clearer communication, early educational programs, ethical practices, and joint outreach efforts, we can enhance financial resilience, informed risk management, and long-term economic stability among adults.